DAYA ANTIBAKTERI KOMBINASI CHITOSAN-MINYAK ATSIRI KAYU MANIS TERHADAP STAPHYLOCOCCUS EPIDERMIDIS DAN PSEUDOMONAS AERUGINOSA SECARA IN VITRO - , KRISTINE BR BERUTU; , dr. Titik Nuryastuti, M.Si., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background : Staphylococcus epidermidis and Pseudomonas aeruginosa are important bacterial that responsible for nasocomial infection and septic. Implant devices in the body can increase the number of infection caused those bacterial. These bacterial highly resistance to several antibiotics so there are diseases that difficult to treat with antibiotics that have been exist. Thatâs the reason why the reaserch about antimicrobial derived from nature is needed, for example chitosan and cinnamon oil. Objectives : To know antibacterial effect of chitosan and cinnamon oil combination on S. epidermidis and P. aeruginosa and to know is there any sinergy activity from both combination. Method : Descriptive experimental. Subjects of the research are chitosan and cinnamon oil. Bacterials tested are S. epidermidis and P. aeruginosa. To know Minimal Inhibit Concentration of chitosan and cinnamon oil combination on isolate S. epidermidis and P.aeruginosa, chequerboard titration test is used. Result : Minimal Inhibit Concentration (MIC) of chitosan combination on siolate S. epidermidis 64, S. epidermidis 236 is 0,00078 Î¼g/ml, S. epidermidis 134 is 0,1 Î¼g/ml, and P. aeruginosa 958 and P. aeruginosa 1105 is 6,25 Î¼g/ml. MIC of cinnamon oil combination for all bacterials are same, 0,0156%. Fractional Inhibit concentration index for all bacterials is under 5 (FICI â¤5), so activity of these two antibacterial is sinergy. Conclusion : Chitosan and cinnamon oil combination has antibacterial effect on isolate S. epidermidis and P.aeruginosa with lower concentration in combination than single and both of antibacterial have sinergy activity.